The making of the Middle Ages - Southern, R. W. 1912-2001 (Yale paperbounds ;, 1964)
A distinguished Oxford historian presents an absorbing study of the main personalities and the influences that molded the history of Western Europe from the late tenth to the early thirteenth century, describing the chief forms of social, political, and religious organization.